2020
DOI: 10.18632/aging.103462
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acylcarnitine levels increase with healthy aging

Abstract: Acylcarnitines transport fatty acids into mitochondria and are essential for β-oxidation and energy metabolism. Decreased mitochondrial activity results in increased plasma acylcarnitines, and increased acylcarnitines activate proinflammatory signaling and associate with age-related disease. Changes in acylcarnitines associated with healthy aging, however, are not well characterized. In the present study, we examined the associations of plasma acylcarnitines with age (range: 20-90) in 163 healthy, non-diseased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 66 publications
2
41
1
1
Order By: Relevance
“…Second, the studied population was older and consisted of more males than the reference population. Impact of age on carnitine concentrations is controversial [ 28 , 29 ]. Gender has been supposed to influence carnitine concentrations [ 28 ], but no differences in C0 and AC concentrations between males and females were observed in the reference population as in the ICU survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the studied population was older and consisted of more males than the reference population. Impact of age on carnitine concentrations is controversial [ 28 , 29 ]. Gender has been supposed to influence carnitine concentrations [ 28 ], but no differences in C0 and AC concentrations between males and females were observed in the reference population as in the ICU survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics studies on aging reported increasing circulating concentrations of acylcarnitines, mostly long-chain, with age [ 43 , 44 ], which could reflect loss in mitochondrial function [ 45 ]. In a study [ 46 ] comparing metabolites in serum samples obtained 7 years apart from the same individuals (KORA S4 and KORA F4), acetylcarnitine and several other acylcarnitines increased in the follow-up samples compared with baseline samples.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites were used as dependent variables, while CAD phenotype and confounders served as independent variables. Regressions using acylcarnitines or carnitine as dependent variable were adjusted for the following confounders age ( 53 , 54 ), sex ( 55 ), HbA1c (%) ( 11 , 56 , 57 ), body fat (%) ( 11 , 58 , 59 ), smoking habits ( 60 ), antihypertensive and lipid lowering medication ( 61 64 ) as well as fasting and sampling time ( Supplementary Figure 1 ) ( 65 67 ). Regressions using BCAAs as dependent variable were adjusted for the following confounders: age, sex ( 67 70 ), skeletal muscle mass ( 71 , 72 ), smoking habits ( 60 , 73 ), sampling time and fasting time ( Supplementary Figure 2 ) ( 65 67 ).…”
Section: Methodsmentioning
confidence: 99%